A clinical study of minor physical anomalies in patients with schizophrenia - Nath, Kamal; Dutta, Mithun; Baruah, Aparajeeta; Naskar, Subrata (International Journal of Research in Medical Sciences, 2016)
Background: Minor physical anomalies (MPA) are unusual morphological deviations that have no serious medical or cosmetic significance to an individual. But however minor they may be, various studies across the world have revealed their significance as a possible endophenotype of schizophrenia. This study is an attempt towards understanding the various sociodemographic and illness correlates as well as the prevalence of MPA in people with schizophrenia. Methods: 100 admitted patients who fulfilled the criteria for schizophrenia as laid down by international classification of diseases version 10 (ICD-10) and other inclusion and exclusion criteria over one year period with age between 16-60 years were included in the study. A standardized semi structured proforma for various sociodemographic and illness variables and Waldrop minor congenital anomaly scale (weighted version) were applied on the study subjects. Data obtained was analyzed using SPSS and chi-square was applied to find out statistical association. Results: Minor physical anomalies were found to be present in only 15% of subjects and they have a statistically significant association with age (p=0.041) and occupation (p=0.002). Conclusions: The study of MPA in schizophrenia is a novel attempt to unearth any subtle associations between the genetic abnormality and its interactions with the various psychophysiological as well as other environmental factors which ultimately leads to the endophenotype and in some cases to the ultimate illness state. In our study the presence of MPA in 15% of the subjects with various degree of severity probably indicates heterogeneity of the schizophrenia illness and a complex interaction with various factors from genotype to phenotype.